2012
DOI: 10.1172/jci60688
|View full text |Cite
|
Sign up to set email alerts
|

CD14 and NFAT mediate lipopolysaccharide-induced skin edema formation in mice

Abstract: Inflammation is a multistep process triggered when innate immune cells -for example, DCs -sense a pathogen or injured cell or tissue. Edema formation is one of the first steps in the inflammatory response; it is fundamental for the local accumulation of inflammatory mediators. Injection of LPS into the skin provides a model for studying the mechanisms of inflammation and edema formation. While it is known that innate immune recognition of LPS leads to activation of numerous transcriptional activators, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 43 publications
1
43
0
4
Order By: Relevance
“…COX2 is known to play a critical role in skin inflammation. Signaling via PGE2 and its receptor induces vascular hyperpermeability and dermal edema (Rundhaug and Fischer, 2008; Zanoni et al , 2012; Morimoto et al , 2014). Our findings that inhibition of COX2 by NDH 4338 was associated with reduced edema and inflammation are consistent with a role for prostaglandins in vesicantinduced skin injury.…”
Section: Discussionmentioning
confidence: 99%
“…COX2 is known to play a critical role in skin inflammation. Signaling via PGE2 and its receptor induces vascular hyperpermeability and dermal edema (Rundhaug and Fischer, 2008; Zanoni et al , 2012; Morimoto et al , 2014). Our findings that inhibition of COX2 by NDH 4338 was associated with reduced edema and inflammation are consistent with a role for prostaglandins in vesicantinduced skin injury.…”
Section: Discussionmentioning
confidence: 99%
“…1). This activation of NFAT family members, in association with TLR4-dependent companion transcription factors, controls the expression of specific genes such as IL-2, Nur77 (Zanoni et al, 2009) and mPGES-1 (Zanoni et al, 2012a). The regulation of these genes affects many DC-related functions.…”
Section: The Cd14-dependent Transcriptional Response To Lpsmentioning
confidence: 99%
“…mPGES-1 is a key enzyme involved in PGE 2 biosynthesis. It has been demonstrated that local PGE 2 production by DCs is implicated in skin edema formation and in the control of free antigen delivery to draining lymph nodes (Zanoni et al, 2012a). The CD14-NFAT pathway controls the expression of IL-2, mPGES-1 and Nur77 (left).…”
Section: The Cd14-dependent Transcriptional Response To Lpsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TLR4 co-receptor CD14 possesses autonomous signalling capacities in DCs and it is able to induce Srcfamily kinases and phospholipase C gamma-2 (PLC␥2) activation, influx of extracellular calcium and calcineurin-dependent nuclear NFAT translocation (Zanoni et al, 2009). The activation of the NFAT pathway in DCs is required to control DC life cycle (Zanoni et al, 2009) and to regulate IL-2 and lipidic pro-inflammatory mediators production (Zanoni et al, 2012). Other PRRs such as DECTIN-1 can also trigger NFAT activation and IL-2 production (Goodridge et al, 2007).…”
Section: Pamp Associated Responses: the Example Of Tlrsmentioning
confidence: 99%